A sensor-fitted suit to analyse stroke patient's movements.
The moment when stroke patients return home after treatment has always been a source of concern for both themselves and their physicians, as the latter are left blind without any feedback. But this is now a thing of the past : a novel suit fitted with 41 sensors is finally ready for commercialisation.